Bomb : the race to build--and steal--the world's most dangerous weapon - Sheinkin, Steve (Scholastic Inc., 2013)
Examines the history of the atom bomb, from the 1938 discovery that the uranium atom could be split through the race to develop, steal, and use the atom bomb in World War II to establish world military dominance by scientists and spies in America, Britain, Russia, and Germany.